The impact of the COVID-19 pandemic on in-hospital mortality in patients admitted through the emergency department - Changgyun Kim; Juncheol Lee; Yongil Cho; Jaehoon Oh; Hyunggoo Kang; Tae Ho Lim; Byuk Sung Ko (Clinical and Experimental Emergency Medicine, 2023)
Objective The COVID-19 pandemic might have adversely affected outcomes of patients in emergency departments (EDs). The aim of this study is to evaluate the impact of the COVID-19 pandemic on in patients admitted through the emergency department. Methods This study is a single-center, retrospective, observational cohort study. We compared the prognosis of patients admitted through the ED before the COVID-19 pandemic (November 2018 to June 2019) and after COVID-19 (November 2020 to June 2021). The primary outcome was in-hospital mortality. Multivariable logistic regression analysis was performed to determine whether the COVID-19 pandemic was independently associated with patient prognosis. Results The number of patients admitted through the ED before and after COVID-19 was 5,333 and 4,625, respectively. The mean ED length of stay before and after COVID-19 was 401 and 442 minutes, respectively (P<0.001). The number of in-hospital deaths before and after COVID-19 were 269 (5.0%) and 322 (7.0%), respectively (P<0.001). Multivariable logistic regression analysis showed that the COVID-19 period was significantly associated with higher in-hospital mortality (adjusted odds ratio, 1.37; 95% confidence interval, 1.12–1.67; P=0.002). Conclusion In the COVID-19 period, in-hospital mortality increased compared to that before COVID-19 among hospitalized ED patients.